2006
DOI: 10.1002/pd.1582
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prenatal diagnosis of common trisomies: discordant results between QF-PCR analysis and karyotype analysis on long-term culture for a case of trisomy 18 detected in CVS

Abstract: We report here an apparently normal CVS QF-PCR result that was completely discrepant with the trisomy 18 positive karyotype result on long-term culture. This has important implications regarding our current testing protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…However, as has already been discussed, according to Grati et al [6] there is a risk of missing some rare cases of type IV discordance that are TFM. As shown from our results and those of most investigators [4,26] if QF-PCR is always followed by LTC the probability of false-negative or false-positive results is negligible.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, as has already been discussed, according to Grati et al [6] there is a risk of missing some rare cases of type IV discordance that are TFM. As shown from our results and those of most investigators [4,26] if QF-PCR is always followed by LTC the probability of false-negative or false-positive results is negligible.…”
Section: Discussionsupporting
confidence: 70%
“…A complete discrepancy in the prediction of fetal trisomies 18 and 21 in CVS by QF-PCR analysis of uncultured villi and karyotyping after LTC is rare, but it has been reported in certain cases [26][27][28][29] . It has also been shown that QF-PCR cannot detect mosaicism at a level lower than 15%, which is rarely the case when full cytogenetic analysis is performed in LTC [4,27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is in line with previous studies demonstrating the cellular complexity of CVS tissues and the relevance of CVS preparation methods for molecular testing to minimize the risk of false-positive or -negative results. 15,16 As such, MLPA analysis of CVS on DNA isolation of whole villi digested with proteinase K as presented here, is only appropriate as a replacement for TK of STC villi. In case 7, in which the abnormal cells were confined to the LTC, the MLPA result for chromosome 18 was indicative for a mosaic trisomy 18, with a 95% CI of 1.08Ϫ1.28.…”
Section: Discussionmentioning
confidence: 99%
“…Dans ce cas, on observe sur les différents marqueurs, des allèles supplémentaires ou des rapports d'allèles biaisés d'un marqueur à l'autre. Pour détecter un mosaïcisme par la méthode QF-PCR, il est nécessaire que la population cellulaire la moins représentée soit au moins de 10-15 % de la population cellulaire étudiée [3]. L'interprétation est déli-cate car la signification d'une mosaïque est difficile.…”
Section: Les Pièges De La Pcr Fluorescente Quantitativeunclassified